Central Reading of Endoscopy Endpoints in Inflammatory Bowel Disease Trials. Issue 10 (October 2015) - Gottlieb, Klaus; Travis, Simon; Feagan, Brian; Hussain, Fez; Sandborn, William J.; Rutgeerts, Paul
Abstract : Background: Central reading of endoscopy (CROE) is crucial in determining who qualifies for a trial but also has a role, independent of the selected scoring system, in decreasing measurement noise that can obscure separation between placebo and active drug. Benefits of CROE may not be independent of the method chosen, and controversy exists about the ideal approach. Methods: Literature review and concept development. Results: Components to be considered in the reading algorithm are blinding, number of central readers, independent voting versus consensus panel, video recordings versus still images, and involvement of the site reader. Key concepts considered are endpoints, bias, power, and sample size derived from the Food and Drug Administration and European Medicines Agency guidelines, as well as the technological requirements and recruitment, qualification, and revalidation of central readers as applied to CROE. Conclusions: Recording and CROE should be standardized, and an imaging charter developed with research on the different components and its overall impact. Abstract : Article first published online 18 June 2015.